New insight into the role of the pathway NLRP1 and NLRP3 inflammasomes and IL-33 in ultraviolet-induced cutaneous carcinogenesis - Lesiak, Aleksandra; Wodz, Karolina; Ceryn, Justyna; Sobolewska-Sztychny, Dorota; Bednarski, Igor; Piekarski, Janusz; Pabianek, Marta; Nejc, Dariusz; Dróżdż, Izabela; Narbutt, Joanna; Noweta, Marcin; Ciążyńska, Magdalena (Frontiers in Medicine, 2025)
IntroductionInflammasomes NLRP1 (NLR family pyrin domain containing 1) and NLRP3 are pivotal regulators of the innate immune response, activated by a spectrum of endogenous and exogenous stressors, including ultraviolet radiation (UVR). The precise molecular mechanisms underlying the activation of these inflammasomes remain unclear. Furthermore, the involvement of interleukin-33 (IL-33) in UVR-induced skin carcinogenesis is not well defined.PurposeThe objective of this study is to evaluate the expression of interleukin genes (IL-33, IL-18, IL-1β) following the activation and silencing of NLRP1 and NLRP3 at various wavelengths and doses of UV radiation, and to correlate these expressions with pertinent tumor markers (e.g., Gli1, Gli2, FOXO3A, SerpinA1, SerpinA3, and EphB2).Methods and materialsCultures of keratinocyte cell lines were exposed to varying doses of UV radiation using specific lamps. To inhibit the expression of NLRP1 and NLRP3 genes, cells were transfected with targeted siRNAs. Gene expression of inflammasome components and effector proteins was quantified using Real-time PCR and ELISA.ResultsThere was a marked upregulation in the expression levels of cytokine genes IL-18, IL-1β, and IL-33 upon exposure to UVB and UVA radiation, compared to non-irradiated keratinocytes. Silencing NLRP1 or NLRP3 via RNA interference in primary human keratinocytes resulted in a significant reduction of cytokine gene expression. Additionally, a notable increase in tumor marker gene expression was observed in cells with functional NLRP1 and NLRP3 following UV radiation, whereas silencing these inflammasome genes altered the expression profiles of these markers.ConclusionThis study provides a pioneering comprehensive assessment of the roles of NLRP1, NLRP3, and IL-33 in the pathogenesis of UV-induced cutaneous carcinogenesis. Our findings substantiate the role of IL-33 as a critical early danger signal elicited in response to inflammatory UV radiation, presumably regulated by inflammasomes.